2022
DOI: 10.3390/ma15020494
|View full text |Cite
|
Sign up to set email alerts
|

Where ppm Quantities of Silsesquioxanes Make a Difference—Silanes and Cage Siloxanes as TiO2 Dispersants and Stabilizers for Pigmented Epoxy Resins

Abstract: In this work, silsesquioxane and spherosilicate compounds were assessed as novel organosilicon coupling agents for surface modification of TiO2 in a green process, and compared with their conventional silane counterparts. The surface-treated TiO2 particles were then applied in preparation of epoxy (EP) composites and the aspects of pigment dispersion, suspension stability, hiding power, as well as the composite mechanical and thermal properties were discussed. The studied compounds loading was between 0.005–0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 45 publications
2
9
0
Order By: Relevance
“…Silicon presence comes from microsilica filler; zirconium from zirconia used mostly as an RTG contrasting agent; titanium from TiO 2 pigment used to balance the composite color; all these elements are in form of oxides, which is visible on oxygen EDS map. The oxides contain hydroxyl surface groups, which allow for chemical reaction with a silane or spherosilicate-based coupling agent (primer) [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Silicon presence comes from microsilica filler; zirconium from zirconia used mostly as an RTG contrasting agent; titanium from TiO 2 pigment used to balance the composite color; all these elements are in form of oxides, which is visible on oxygen EDS map. The oxides contain hydroxyl surface groups, which allow for chemical reaction with a silane or spherosilicate-based coupling agent (primer) [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Spherosilicate compounds were prepared according to literature reports: octahydrospherosilicate [ 29 ]; mixed group spherosilicates [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The variation of surface nature was also observed when titanium dioxide was functionalized with sodium stearate and sodium oleate [ 17 ]. Recent studies have shown that the use of functionalized silsesquioxanes as modifiers of TiO 2 increased its hydrophobicity and improved covering and dispersing properties [ 18 ].…”
Section: Introductionmentioning
confidence: 99%